The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/bip.22569
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐anionic phosphopeptides produced by unexpected histidine alkylation exhibit high plk1 polo‐box domain‐binding affinities and enhanced antiproliferative effects in hela cells

Abstract: Binding of polo-like kinase 1 (Plk1) polo-box domains (PBDs) to phosphothreonine (pThr)/phosphoserine (pSer)-containing sequences is critical for the proper function of Plk1. Although high-affinity synthetic pThr-containing peptides provide starting points for developing PBD-directed inhibitors, to date the efficacy of such peptides in whole cell assays has been poor. This potentially reflects limited cell membrane permeability arising, in part, from the di-anionic nature of the phosphoryl group or its mimetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…14 More importantly, we have also shown that the pThr residue in 5 can be replaced with Pmab to produce a phosphatase-stable peptidomimetic (peptide 7 ) having complete retention of inhibitory potency. 13,15,16 Unfortunately, the use of Pmab in further ligand development is significantly hindered by relatively inefficient synthetic access to orthogonally-protected Pmab constructs that are compatible with solid-phase peptide synthesis (SPPS). In this work, we have developed a more direct synthetic route to SPPS-compatible Pmab analogs.…”
mentioning
confidence: 99%
“…14 More importantly, we have also shown that the pThr residue in 5 can be replaced with Pmab to produce a phosphatase-stable peptidomimetic (peptide 7 ) having complete retention of inhibitory potency. 13,15,16 Unfortunately, the use of Pmab in further ligand development is significantly hindered by relatively inefficient synthetic access to orthogonally-protected Pmab constructs that are compatible with solid-phase peptide synthesis (SPPS). In this work, we have developed a more direct synthetic route to SPPS-compatible Pmab analogs.…”
mentioning
confidence: 99%
“…Accordingly, increasing cellular bioavailability of PBD-binding inhibitors represents an active area of investigation. 28 Our current peptides are not clinically relevant, due in part to poor bioavailability. However, given the extreme enhancement in overall ligand affinity that can be achieved by accessing the cryptic pocket, we believe that optimizing interactions within this region may be highly relevant to developing more bioavailable agents.…”
Section: Discussionmentioning
confidence: 98%
“…In order to address this problem, peptide 4j was selected, due to its high Plk1 PBD–binding affinity and its selectivity, and the fact that its alkylphenyl group is located on the His residue, which is situated proximal to the minimal key “SpT” recognition motif [120]. It was found that, while the replacement of the pThr residue in 4j with non-phosphorus-containing acidic residues results in a dramatic loss of Plk1 PBD–binding affinity, use of the phosphonic acid–based pThr mimetic, Pmab [139], can be accomplished with complete retention of binding affinity [126, 140]. Whole-cell studies with the PEGylated Pmab-containing version of 4j (designated as 4j* ) showed that effective mitotic block in cultured HeLa cells could be achieved, but only at high extracellular concentrations (IC 50 = 320 μM), indicating poor cellular uptake [120, 126].…”
Section: Targeting the Pbd Of Plk1mentioning
confidence: 99%